Aflatoxin contamination of maize flour in Kenya: Results from multi-city, multi-round surveillance - Barasa, Allan; Hoffmann, Vivian; Murphy, Mike; Ndisio, Boaz; Okoth, Sheila A. (International Food Policy Research Institute, 2023)
This research was undertaken to characterise the level and distribution of aflatoxin contamination of maize flour, a key food safety concern in Kenya. More than 1,200 samples of maize flour were collected and analyzed over the course of one year, allowing a robust characterization of relative risk across geography and product type. Informally milled flour was found to be significantly more contaminated than branded flour, a result attributable to the refining process applied to this flour. The results of this study can be used to inform messaging to consumers about the relative riskiness of informally versus formally milled flour, and for geographical targeting of resources for aflatoxin mitigation.